(untitled) (diségno, 2022)
For the centenary of the birth of Marcello D’Olivo (1921-1991) we started an activity of geometric analysis and reconstruction of some of his important works with the aim of establishing a digital archive –interactively explorable both in presence and at a distance– to tell the multifaceted production of the Friulian professional in the national and international architectural panorama. A first result was presented at the exhibition Homage to Marcello D’Olivo. Geometries, tactile models, virtual reality organized at the Polo Scientifico Tecnologico of the University of Udine in December 2021. Based on drawings kept at the Gallerie del Progetto of Palazzo Valvason Morpurgo in Udine, which houses most of the architect’s drawings, and belonging to private collections, the research has been oriented to the digitization and three-dimensional modelling of realized and unfinished architectural complexes, with a triple purpose: on the one hand to reveal and document the intimate geometric system of volumes as a fundamental teaching tool; on the other hand, to use these models to experiment with new technologies of interactive navigation and dynamic exploration through virtual reality interfaces; a third aim is dissemination on the territory, creating physical models in rapid prototyping, to allow the user a haptic perception according to the directives of the “Design for all” that provide to replace the imperative prohibition to tactically use the models in museums the most inclusive ‘forbidden not to touch’.